THE CONCEPT OF MEDIA EDUCATION IN HIGHER EDUCATION: MODELS, AND DEVELOPMENT TRENDS - Qodirova Sharifa Nigmatullayevna, Kenjaboyeva Nigora (International Journal of Literature and Language Studies, 2026)
This article scientifically analyzes the formation of the media education concept in the higher education process, its theoretical and methodological foundations, leading pedagogical approaches, existing models, and global development trends. The effectiveness of using media tools in higher education, international experience in media education practices, and opportunities for developing media education in Uzbekistan’s higher education system were studied. Within the framework of the research, a survey was conducted among 150 teachers and 320 students across 9 different higher education institutions, and the current state, needs, and proposals regarding media education were analyzed. The results demonstrated that media education significantly improves lesson effectiveness, students’ information consumption culture, creative thinking, and critical analysis skills. At the end of the article, scientifically grounded recommendations for further improvement of media education in higher education are presented